2009
DOI: 10.1021/bc800534r
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugation and Detection of Lactosamine Moiety using α1,3-Galactosyltransferase Mutants That Transfer C2-Modified Galactose with a Chemical Handle

Abstract: Studies on wild-type and mutant glycosyltransferases have shown that they can transfer modified sugars with a versatile chemical handle, such as keto or azido group, that can be used for conjugation chemistry and detection of glycan residues on glycoconjugates. To detect the most prevalent glycan epitope, N-acetyllactosamine (LacNAc (Galβ1-4GalNAcβ)), we have mutated a bovine α1,3-galactosyltransferse (α3Gal-T)1 enzyme which normally transfers Gal from UDP-Gal to the LacNAc acceptor, to transfer GalNAc or C2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…1 a Consequently, their C2-carbon isosteres, C2-ketonylsugars such as 2-ketoGlc, 2-ketoMan, and 2-ketoGal, have been synthesized for the development of antibiotics 2 and to study cell surface recognition, metabolic pathways, and the mechanism of polysaccharide formation and protein post-translational modifications. 3 However, the preparation of C2-ketonylsugars is labor-intensive and time-consuming. It requires an 8-step procedure with less than 21% overall yield, multiple protection/deprotection protocols, and the use of toxic alkyl tin and OsO 4 reagents ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 a Consequently, their C2-carbon isosteres, C2-ketonylsugars such as 2-ketoGlc, 2-ketoMan, and 2-ketoGal, have been synthesized for the development of antibiotics 2 and to study cell surface recognition, metabolic pathways, and the mechanism of polysaccharide formation and protein post-translational modifications. 3 However, the preparation of C2-ketonylsugars is labor-intensive and time-consuming. It requires an 8-step procedure with less than 21% overall yield, multiple protection/deprotection protocols, and the use of toxic alkyl tin and OsO 4 reagents ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…22 We have previously shown that mutations in a few residues in the sugar donor-binding site of glycosyltransferases broaden their sugar donor specificities. 12,3132 Mutation of Tyr289 to Leu289 in bovine β4Gal-T1 enzyme, the Y289L-β4Gal-T1 mutant, accommodates a Gal with a C2-N-acetyl group (GalNAc) or a chemical handle that is similar in size and shape to it, such as a C2-keto- or C2-azido group. 22 Also, it had been shown that the metal ion specificity in β4Gal-T1 is determined by the Met-344 residue and that mutating Met-344 to a His-344 residue changes the metal ion specificity of the resulting mutant enzyme, M344H-β4Gal-T1, from Mn 2+ to Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the Leu/Met266 proved to be crucial in the A/B donor substrate specificity, so that a significant change in the corresponding specificity constants could be observed by a single amino acidic mutation [154]. These findings have been applied recently also to the design of novel GTs with broader donor specificities to transfer sugar residues with a chemically reactive handle, such as a keto or azido group, from the corresponding UDP-sugar analogues [155,156]. In the case of bovine a-1,3-GalT, mutants 280 SGG 282 and 280 AGG 282 with the highest GalNAcT activity (about 10-20% of the initial GalT activity) have been exploited for transferring 2-keto-Gal or GalNAz (Gal-2-NH-CO-CH 2 -N 3 ) to LacNAc (Gal-b-1,4-GlcNAc) terminal moieties of glycoconjugates (Scheme 10.9).…”
Section: Substrate Specificity and Synthetic Applicationsmentioning
confidence: 94%